How do health professionals prioritize clinical areas for implementation of evidence into practice? A cross-sectional qualitative study. Issue 3 (26th September 2020) - Wenzel, Lisa-Anabell; White, Jenni; Sarkies, Mitchell N.; Morris, Meg E.; Carey, Leeanne; Williams, Cylie; Taylor, Nicholas F.; Martin, Jenny; Bardoel, Anne; Haines, Terry P.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Aim: The current study aimed to identify and understand the reasons why allied health professionals think certain areas of healthcare service provision are a high priority for implementation of evidence into practice. Methods: A cross-sectional online survey using open-ended questions was conducted between April and May 2018 to identify potential areas for practice change and characterize how participants justified identified areas of priority. Eligible participants were invited by email and included allied health professionals from public or private health services, governance agencies and universities across Australia. Responses were analysed using qualitative content analysis. Results: There were 149 surveys commenced with 146 respondents completing the survey. Of the 146 respondents, 128 were female, 17 male and one unknown. Most of the respondents were between 40 and 49 years old and had a master's degree. In total respondents from more than 13 different professions completed the survey with 110 respondents having more than 10 years of experience in allied health. Ten themes emerged outlining the main reasons respondents felt that their nominated areas of practice change were a high priority for action. These included closing gaps between practice and policy/recommendation/guideline; closing research evidence to practice gaps; improving access to services; perceived cost-effectiveness of service delivery; improving effectiveness of allied health services; current imbalance between service supply and demand; amount of resources involved in service delivery; extent of the health problem; areas of allied health care futility; and equality of workload across allied health professionals. Conclusion: The current research provides insights into the decision-making processes of allied health professionals when prioritizing areas of clinical practice for implementation of evidence into practice. Despite an appetite for evidence-based practice, behaviour change was not always implemented in a consistent and systematic manner. There was variability in the type and application of evidence used by allied health professionals to support clinical practice. Whether a more systematic approach to research translation fosters evidence uptake awaits confirmation. Also awaiting investigation are the economic and societal impacts of consistently implementing research-informed clinical decision-making.